The effect of perceived stress on the relationship between perfectionism and burnout in coaches - Tashman, L. S.; Tenenbaum, G.; Eklund, R. (Anxiety, Stress and Coping, 2010)
The effects of perceived stress (PS) on the relationship between adaptive and maladaptive forms of perfectionism and burnout were examined. Smith's (1986) stress appraisal model and Kelley, Eklund, and Ritter-Taylor's (1999) model of coach burnout were used to test two models of burnout in a sample of college coaches (N=177). The results indicated that there is an indirect effect of self-evaluative perfectionism (i.e., maladaptive form of perfectionism) on burnout through PS as well as a significant direct link to burnout, accounting for 56% of its variance. In contrast, conscientious perfectionism (CP) (i.e., adaptive perfectionism) did not directly impact burnout, nor was there an indirect effect through PS. Based on Lazarus's (1999) ideas about stress appraisal, the results suggested that maladaptive forms of perfectionism resulted in more threatening perceptions of stress, thus, potentially leading to the experience of burnout. However, adaptive forms of perfectionism did not seem to result in increased appraisals of stress or result in burnout. The results did indicate a significant correlation between the two forms of perfectionism, which may explain why CP did not significantly impact PS or burnout.